2015
DOI: 10.1007/s40618-015-0369-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid accumulation product and metabolic syndrome: a population-based study in northern Iran, Amol

Abstract: LAP has a strong and reliable diagnostic accuracy for MetS in Iranian population in the north of Iran. LAP showed a better predictability than other obesity indexes assessed in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 24 publications
12
53
5
3
Order By: Relevance
“…In addition, in fact, men have, on average, more visceral fat and less subcutaneous fat [39]. In our results, the LAP index was the parameter with the highest sensitivity discriminating individuals with and without MetS in the ROC curve, with AUC 0.9489 ( Figure 7 and Figure 8), which is consistent with several population studies conducted in individuals from China [41,42] and Iran, which showed the same conclusions [29], similarly to Abruzzese et al [43] in a population of Latin America, found similar results, with similar cutoff points for different populations and ethnic groups. In this study, LAP and VAI were acceptable indicators for MetS screening, however LAP presented a better correlation between WC and triglyceride values, whereas VAI was the index that was worse correlated with the rest of the variables that make up ( Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, in fact, men have, on average, more visceral fat and less subcutaneous fat [39]. In our results, the LAP index was the parameter with the highest sensitivity discriminating individuals with and without MetS in the ROC curve, with AUC 0.9489 ( Figure 7 and Figure 8), which is consistent with several population studies conducted in individuals from China [41,42] and Iran, which showed the same conclusions [29], similarly to Abruzzese et al [43] in a population of Latin America, found similar results, with similar cutoff points for different populations and ethnic groups. In this study, LAP and VAI were acceptable indicators for MetS screening, however LAP presented a better correlation between WC and triglyceride values, whereas VAI was the index that was worse correlated with the rest of the variables that make up ( Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…The published population studies that have used the fats indexes in the early detection of MetS and other cardiovascular risks in individuals distributed according to gender and race (African American, Caucasian, Asian, Hindu) have encouraging results, showing that they are superior to BMI and WC [24,28,29]. In the Venezuelan population, no published studies were available to validate the use of fats indexes; however, it was found that Barrios and Rivero used the Body Adiposity Index (BAI) in 90 patients from the Lara state, concluding that BAI did not represent a reliable index to determine new cases of MetS [30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two studies 22,26 did not adequately define the age group of the elderly. While Motamed et al 26 did not stratify the results between adults and the elderly, Tellechea et al 22 considered the elderly group to be aged between 45 and 65. These facts limit the understanding of this indicator's performance, specifically among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Tellechea et al 22 , Chiang & Koo 24 and Motamed et al 26 also observed the high predictive capacity of LAP to identify MetS (AUC higher than 0.90). Among these studies, the lowest LAP cut-off point to identify MetS was reported by Chiang & Koo 24 (31.6 for both sexes).…”
Section: Clinical Indicatorsmentioning
confidence: 92%
See 1 more Smart Citation